3D/1D Amine Functionalized MIL-125/TiO2 NWs Metal-organic Framework Heterostructures for Solar Stimulated CO2 Reduction to Green Fuels - Ji Zhang Tai; Wei Keen Fan; Hajar Alias; Amnani Shamjuddin; Mohamad Sukri Mohamad Yusof; Abdul Rahman Mohamed; Muhammad Tahir (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
The urgent need to mitigate atmospheric CO2 and transition toward renewable energy has spurred growing interest in photocatalytic CO2 hydrogenation. In this work, we report on the fabrication of a novel 3D/1D NH2-MIL-125/TiO2 nanowire (NWs) heterostructure via a straightforward mechanical assembly method, combining the excellent visible light absorption of amino-functionalized metal-organic frameworks (MOFs) with the robust charge transport properties of one-dimensional TiO2 NWs. Structural and optical characterisations have confirmed on intimate interfacial contact and synergistic electronic interactions between the MOF and TiO2, forming an S-scheme heterojunction which promotes an enhanced photogenerated carrier separation. Under visible light, the optimised 5 wt% NH2-MIL-125/TiO2 NWs composite achieved methane and CO yields of 13.98 μmol/g and 84.76 μmol/g, respectively. Notably, CH4 production soared to 660.47 μmol/g under solar-simulated irradiation, representing a 47-fold enhancement. This significant performance boost is attributed to improved light harvesting, facilitated electron migration, and strengthened interfacial dynamics. This study provides a scalable and efficient strategy for designing hybrid MOF-semiconductor photocatalysts, offering a promising pathway for sustainable solar fuel generation. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).